The Impact of Ecotourism on Local Community Income: Case Study of the Wisata Alam Taman Rusa in Aceh Besar Regency - Dedi Sufriadi; Nadiatul Husna; Rizka Rizka; Zakaria Zakaria; Mawardi Mawardi (Jurnal Ragam Pengabdian, 2026)
Ecotourism is a form of sustainable tourism that has the potential to provide economic benefits to local communities while maintaining environmental sustainability. The presence of ecotourism destinations is expected to create business and employment opportunities that can improve the welfare of surrounding communities. This study aims to examine the impact of ecotourism on the income of local communities around the Wisata Alam Taman Rusa tourism destination in Aceh Besar Regency. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The informants consisted of village officials, tourism managers, business owners, workers, and other relevant stakeholders selected purposively. Data were analyzed through data reduction, data display, and conclusion drawing, supported by SWOT analysis to identify internal and external factors influencing tourism development. The findings indicate that the existence of Wisata Alam Taman Rusa has positively affected local community income through the creation of business opportunities and employment. In addition, tourism activities contribute to village revenue and support local economic development. Therefore, sustainable ecotourism management has significant potential to enhance the welfare of local communities.